Total Intravenous Anaesthesia (TIVA) in Supratentorial Meningioma Undergoing Craniotomy Tumour Removal : A Case Report - Herman, Awanda; Hidayat, Nopian; Anggraeni, Novita; Ananda, Pratama (Universitas Muhammadiyah Surakarta, 2024)
Meningiomas are tumours that grow inside the head cavity or intra-cranial tumours, The incidence of intra-cranial tumours in patients of all ages is approximately 4.2 - 5.4 /100,000. The brain uses 20% of the body's total oxygen. The brain uses most of its oxygen consumption (60%) to generate adenosine triphosphate (ATP), which supports the electrical activity of neurons. In cranitomy tumour removal, it is expected that good oxygen supply and oxygen consumption by the brain are reduced by reducing electrical activity in the brain with the aim of relaxing the brain, Selection of 4 intravenous anaesthetic agents in craniotomy tumour removal in this patient in the form of Tiopental, Fentanyl, Rocuronium and Dexmedetomidine because the use of these agents is the best in reducing cerebral metabolic rate (CMR) and cerebral blood flow (CBF) so as to reduce intracranial pressure (ICP) which appears in this case stable hemodynamics and adequate depth of anaesthesia during surgery.